Management of Automotive Engine Based on Stable Fuzzy Technique with Parallel Sliding Mode Optimization - Farzin Piltan; Mansour Bazregar; Mehdi Akbari; Mojdeh Piran (Institute of Advanced Engineering and Science, 2013)
Both fuzzy logic and sliding mode can compensate the steady-state error of proportional-derivative (PD) method. This paper presents parallel sliding mode optimization for fuzzy PD management. The asymptotic stability of fuzzy PD management with first-order sliding mode optimization in the parallel structure is proven. For the parallel structure, the finite time convergence with a super-twisting second-order sliding-mode is guaranteed.